Design of a long slot antenna - Teo, Ken Wei. (2012)
Recent years has shown vast progress in the development of mobile communication devices, resulting in a particular, continuous reduction in handset size. In order to facilitate this, there is a need for a similar development of small and low profile antennas. The challenge therefore, is to maintain the low profile characteristics while concurrently improving the bandwidth of the antenna. There are many kinds of antennas; however the student will be focusing on long slot antennas in particular for this research.